Limitations in the Effectiveness of United States Economic Sanctions in Altering Russian Behavior in the Russia -Ukraine Conflict, 2014 -2022 - Azizah Amalia; Pantri Muthriana Erza Killian; Dewa Ayu Putu Eva Wishanti (MASI Mandiri Edukasi, 2026)
Economic sanctions are widely used as instruments of international coercion, yet their ability to generate political compliance remains contested. The Russia -Ukraine conflict provides an important case because extensive U.S. sanctions imposed against Russia since 2014 have created significant economic pressure but have not resulted in substantial changes in Russian strategic behavior. This study addresses the gap in sanctions research by examining why economic costs do not always translate into behavioral change. This study aims to explain the limited effectiveness of U.S. economic sanctions against Russia during the 2014 - 2022 Russia-Ukraine conflict and to identify the factors enabling Russia to resist sanctions pressure. Using a qualitative explanatory approach with an embedded single-case study design, this research analyzes documentary data from government documents, international organizations, academic publications, and institutional reports. Data were examined through directed qualitative content analysis and process tracing based on Drezner’s economic coercion framework. The findings show that U.S. sanctions were effective in imposing economic costs by restricting Russia’s access to finance, technology acquisition, and international economic integration. However, their effectiveness in producing behavioral change remained limited because Russia developed adaptive capacities through energy revenues, reserve management, import substitution, domestic institutional adjustment, and economic cooperation with non-Western partners. This study concludes that sanctions should not be evaluated solely by whether they produce political compliance. Instead, sanctions may succeed in imposing costs and constraining capabilities while failing to alter state behavior. The study contributes to economic coercion literature by highlighting the importance of target-state resilience, adaptation mechanisms, and strategic expectations in determining sanctions outcomes.